Human Remains in the History of Anthropology: status, uses, and values - Dias, N. (Changing Ethics in Adressing Human Remains, 2023)
Abstract: Human remains in museum collec8ons are considered a burden and a legacy of unequal power relationships. Therefore, a thorough historical and contextualized analysis of the provenance of human skeletal remains and of the diverse meanings and ethical implications of the term human remains might provide a more nuanced and complex perspective. The presentation will focus on one hand, on the processes through which human remains counted as evidence as well as on the use of human remains as evidence in anthropology. On the other hand, it will explore the changing conceptual contents of the term human remains entailing an awareness of culturally diverse forms of treating dead bodies. These changes also reflect the ethical issues regarding the extension of the concepts of human dignity and respect for the mortal remains of the dead. Thus, the different values involved in the current debates on human remains need to be situated in a broad comparative and historical perspective.